The English Reading Strategies of Two Colombian English Preservice Teachers - Ángela López Velásquez; María Cristina Giraldo (Ikala: Revista de Lenguaje y Cultura, 2011)
This study focuses on the findings of a research project that aimed at identifying the English reading comprehension strategies used by two preservice English teachers, one a successful reader and the other one a less successful reader. The participants were students of a B.Ed. undergraduate program at a public university located in the Colombian Eje Cafetero. Methodological procedures included the collection of reading data through think-aloud protocols, and analysis was based on the constant-comparative method (Glaser & Strauss, 1999).